2020
DOI: 10.1016/j.ekir.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Belatacept to Another Immunosuppressive Regimen in Maintenance Kidney-Transplantation Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Only one study has reported a multicentric series of 44 patients converted from belatacept to another immunosuppressive drugs [ 27 ]. Results showed a significant decrease in eGFR from 44 to 36 mL/min/1.73 m 2 and the authors concluded that belatacept should not be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported a multicentric series of 44 patients converted from belatacept to another immunosuppressive drugs [ 27 ]. Results showed a significant decrease in eGFR from 44 to 36 mL/min/1.73 m 2 and the authors concluded that belatacept should not be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, whether CNI avoidance should be indefinitely continued once kidney function improved had never been addressed. Only one study has reported a multicentric series of 44 patients converted from belatacept to another immunosuppressive drugs 26 . Results showed a significant decrease in eGFR from 44 to 36 ml/min/1.73m2 and the authors concluded that belatacept should not be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…drug injections. While some centers converted patients back to oral immunosuppressive protocols [ 2 ] others initiated a specific infection control protocol [ 3 ]. In the current issue of Transplantation International two French transplant centers [ 4 ] describe an alternative approach and converted 176 patients from maintenance 5 mg i.v.…”
mentioning
confidence: 99%